Opportunities and Challenges of Sharia Fintech (Financial Technology) in Indonesia - Asyifa, Nahdiyatul (UMBanjarmasin, 2023)
Currently, the development of Islamic fintech (financial technology) in Indonesia is growing rapidly. But on the other hand, there are some phenomena and problems in conventional fintech that have a negative impact on society. Therefore, the existence of sharia fintech should be a solution to this phenomenon. The purpose of this research is to find out about the opportunities and challenges of sharia fintech (Financial Technology) in Indonesia. This research uses descriptive analysis with a qualitative approach. The data analysis technique used is the interactive model. The results showed that there are opportunities and challenges of sharia fintech in Indonesia consisting of: regulation, human resources, and mastery of technology from the community.